Social prediction errors in assisting strangers: the role of outcomes and contexts - Li, Yan; Liu, Zhiwei (Frontiers in Psychology, 2025)
IntroductionHelping behavior is a fundamental aspect of social interaction, yet little is known about how accurately helpers can predict the emotional responses of help-seekers, particularly when interacting with strangers.MethodsThis study investigated social prediction errors in helping behavior between strangers and examined how outcomes and contexts influence these errors. In three scenario-based experiments, we assessed helpers’ predictions and help-seekers’ evaluations of gratitude, satisfaction, enthusiasm, and competence across different helping situations.ResultsOur findings reveal consistent underestimation of help-seekers’ positive emotions by helpers, with the degree of underestimation varying based on the outcomes and contexts of the helping behavior.DiscussionThe results demonstrate that social prediction errors in helping behavior are context-dependent and outcome-based, highlighting the complexity of social cognition in prosocial behavior.